Effect of recovery processes on electrical resistivity and martensitic transformations in TiNi-based alloys after ECAP and "abc"-pressing; Advanced Metals, Ceramics and Composities; Part 1 - Baturin A. A.; Lotkov A. I.; Grishkov V. N.; Kopylov V. I.; Kuznetsov P. V. Pavel Viktorovich (2013, 2013)
В фонде НТБ ТПУ отсутствует